Subjective evaluation and acoustic quality in urban axes of San Miguel de Tucumán - Juarez, Isabel del Valle (2025)
Sounds, in a given context, influence the quality of life of its inhabitants. When these sounds cause discomfort to the user and/or affect their health, this is known as noise or acoustic pollution. The soundscape allows us to evaluate this sound context, using it as a tool for conservation, valuation and awareness of the environment, achieving the quality of the habitat. This work deals with the study, from a qualitative approach, on the perception and attitudes of the inhabitants regarding the environmental noise problem in San Miguel de Tucumán. Closed, face-to-face surveys were carried out on site to inhabitants, users and passers-by of the different areas, inquiring about different perceptual and experiential aspects of the different urban axes. From the data obtained, the importance attributed to noise, the level of awareness of the phenomenon, its causes and various effects were determined.